Efektivitas Permainan Edukatif Healthy Plate Puzzle terhadap Pengetahuan Anak Tentang Jajanan Sehat di Sekolah Dasar Daerah Sub-Urban - Ratu Adelline Hania; Fadliyana Ekawaty; Meinarisa Meinarisa; Suryati Suryati; Lisa Anita Sari (SENTRI: Jurnal Riset Ilmiah, 2025)
Healthy snacking knowledge is essential for supporting children’s nutritional status and preventing unhealthy eating habits, particularly in suburban areas where access to diverse food options is increasing. This study aimed to determine the effectiveness of the Healthy Plate Puzzle educational game in increasing elementary school students’ knowledge about healthy snacks. This quantitative study employed a quasi-experimental design with a pre-test and post-test approach involving intervention and control groups. The research was conducted in October 2025 in a suburban area of Senaung village at SDN 003/IX, SDN 45/IX and MI Jauharul Iman Senaung with 74 students selected using total sampling. Knowledge was measured using a validated (r = 0.362–0.699) and reliable (Cronbach’s alpha = 0.735) 20-item questionnaire. Data were analyzed using the Mann-Whitney test to determine differences in knowledge scores before and after the intervention. In the intervention group, the pre-test results showed that most students were in the low knowledge category, with the mean score increasing from 9.72 to 13.83 (a 4.11-point difference). In the control group, the mean score increased from 10.32 to 12.32 (a 2-point difference). The Mann-Whitney test indicated a significant difference in students’ knowledge scores in both the intervention group (Z = –5.605; p = 0.001) and the control group (Z = –3.351; p = 0.001). The Healthy Plate Puzzle educational game is effective in improving students’ knowledge about healthy snacks. This interactive media is recommended as an innovative nutrition education tool for elementary schools to support healthy eating habits.